Vaccines: Shaping global health. Issue 12 (14th March 2017) - ,; Datla, Mahima; Gao, Steven; Homma, Akira; Meng, Li; Suhardono, Mahendra; Suri, Rajinder; Tippoo, Patrick; Pagliusi, Sonia; Ting, Ching-Chia; Lobos, Fernando
Abstract: The Developing Countries Vaccine Manufacturers' Network (DCVMN) gathered leaders in immunization programs, vaccine manufacturing, representatives of the Argentinean Health Authorities and Pan American Health Organization, among other global health stakeholders, for its 17th Annual General Meeting in Buenos Aires, to reflect on how vaccines are shaping global health. Polio eradication and elimination of measles and rubella from the Americas is a result of successful collaboration, made possible by timely supply of affordable vaccines. After decades of intense competition for high-value markets, collaboration with developing countries has become critical, and involvement of multiple manufacturers as well as public- and private-sector investments are essential, for developing new vaccines against emerging infectious diseases. The recent Zika virus outbreak and the accelerated Ebola vaccine development exemplify the need for international partnerships to combat infectious diseases. A new player, Coalition for Epidemic Preparedness Innovations (CEPI) has made its entrance in the global health community, aiming to stimulate research preparedness against emerging infections. Face-to-face panel discussions facilitated the dialogue around challenges, such as risks of viability to vaccine development and regulatory convergence, to improve access to sustainable vaccine supply. It was discussed that joint efforts to optimizing regulatory pathways in developing countries, reducing registration time by up to 50%, are required. Outbreaks of emerging infections and the global Polio eradication and containment challenges are reminders of the importance of vaccines' access, and of the importance of new public-private partnerships.